Brain Abscess and Keratoacanthoma Suggestive of Hyper IgE Syndrome - Soheyla Alyasin; Reza Amin; Alireza Teymoori; Hamidreza Houshmand; Gholamreza Houshmand; Mohammad Bahadoram (Case Reports in Immunology)
Hyper immunoglobulin-E (IgE) syndrome is an autosomal immune deficiency disease. It is characterized by an increase in IgE and eosinophil count with both T-cell and B-cell malfunction. Here, we report an 8-year-old boy whose disease started with an unusual skin manifestation. When 6 months old he developed generalized red, nontender nodules and pathologic report of the skin lesion was unremarkable (inflammatory). Then he developed a painless, cold abscess. At the age of 4 years, he developed a seronegative polyarticular arthritis. Another skin biopsy was taken which was in favor of Keratoacanthoma. Laboratory workup for immune deficiency showed high eosinophil count and high level of immunoglobulin-E, due to some diagnostic criteria (NIH sores: 41 in 9-year-olds), he was suggestive of hyper IgE syndrome. At the age of 8, the patient developed an abscess in the left inguinal region. While in hospital, the patient developed generalized tonic colonic convulsion and fever. Brain computed tomography scan revealed an abscess in the right frontal lobe. Subsequently magnetic resonance imaging (MRI) of the brain indicated expansion of the existing abscess to contralateral frontal lobe (left side). After evacuating the abscesses and administrating intravenous antibiotic, the patient’s condition improved dramatically and fever stopped.